Endoscopic ultrasound-guided gastro-enteric anastomosis for malignant gastric outlet obstruction: Initial experience in an endoscopic center in Lima-Peru - Chirinos-Vega, Juan Antonio (2025)
Endoscopic ultrasound-guided gastroenterostomy is a novel, minimally invasive technique used to palliate malignant gastric outlet obstruction (GOO). Utilizing lumen-apposing metal stents (LAMS), the procedure aims to create a communication between the gastric cavity and a jejunal or duodenal loop, offering low morbidity, fewer adverse events, and rapid symptom relief. The causes of GOO include tumors originating in the gastric antrum, duodenum, major papilla, pancreatic head, and distal bile duct. These conditions commonly present symptoms such as postprandial vomiting, abdominal pain, weight loss, early satiety, and abdominal distension. EUS-GE has emerged as an alternative to traditional approaches such as self-expanding metal stent placement and surgical gastrojejunostomy.